2020
DOI: 10.1093/ajcn/nqz280
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effects of different types of tree nut consumption on blood lipids: a network meta-analysis of clinical trials

Abstract: Background Recent evidence has confirmed that nuts are one of the best food groups at reducing LDL cholesterol and total cholesterol (TC). However, the comparative effects of different types of nuts on blood lipids are unclear. Objectives This network meta-analysis of randomized clinical trials aimed to assess the comparative effects of walnuts, pistachios, hazelnuts, cashews, and almonds on typical lipid profiles. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 51 publications
2
19
1
Order By: Relevance
“…Nut and peanut consumption have been related to improvements on lipid profile [ 16 , 42 ], glycemic control [ 43 , 44 ], and weight loss/no weight gain [ 45 , 46 ] in primary cardiovascular prevention. In addition, including these foods on daily menu have been associated with higher diet quality in primary [ 47 ] and secondary cardiovascular prevention [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nut and peanut consumption have been related to improvements on lipid profile [ 16 , 42 ], glycemic control [ 43 , 44 ], and weight loss/no weight gain [ 45 , 46 ] in primary cardiovascular prevention. In addition, including these foods on daily menu have been associated with higher diet quality in primary [ 47 ] and secondary cardiovascular prevention [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Trials with non-randomized design, quasi-experimental studies, trials conducted in adolescents (under 18 years of age), pregnant and lactating women, those that applied an active control group with possible effects on blood pressure ( e . g , nuts vs fruit or nuts vs omega-3) (16), trials that did not specify the amount of nuts consumption in the control group ( e . g , control group was usual or healthy diet without reporting the amount of nuts consumption), as well as trials that compared the effects of two different types of nuts ( e .…”
Section: Methodsmentioning
confidence: 99%
“…All individual nuts except cashews reduced LDL-cholesterol to a similar extent than reported for total nuts in the mentioned systematic reviews [ 9 , 67 ], but cashews had no effect, which may be due to the low number of RCTs analyzed. Finally, a recent network meta-analysis of 34 RCTs of these five nuts for lipid outcomes used analyses based on the surface under the cumulative ranking curves and concluded that diets enriched in pistachios and walnuts were best for lowering LDL-cholesterol and triglycerides compared with the other nut-enriched diets included in the study [ 75 ].…”
Section: Nut Consumption and Health Outcomesmentioning
confidence: 99%